Quality of life among HIV-infected individuals failing first-line antiretroviral therapy in resource-limited settings - Torres, Thiago S. (2018)
Center for Biostatistics in AIDS Research. Harvard T. H. Chan School of Public Health. Boston, MA, USA / Fundação Oswaldo Cruz. Instituto Nacional de Infectologia Evandro Chagas. Rio de Janeiro, RJ, Brasil.